Multiple Influences of Paleogeography, Sequence Stratigraphy, and Fold Structure on Coalbed Methane Accumulation in the Lopingian (Late Permian) of Junlian Coalfield, SW China - Xiangdong Gao; Wuzhong Li; Yiming Yang; Kaigui Yin; Shihao Zhou (Geofluids)
Junlian coalfield is one of the main targets for coalbed methane (CBM) exploration and development in the southwest China. Based on field geological survey, core observation, gas content statistics, coal maceral composition, vitrinite reflectance (RO), proximate analysis and trace element test, lithological types, lithofacies, sedimentary environment, and structural analysis, this research established the sequence stratigraphy frame, revealed the plane distribution characteristics of sedimentary facies, and defined CBM accumulation mode. The results show that six rock types were identified and further subdivided into twenty lithofacies types. Four types of sedimentary systems such as alluvial plains, delta, lagoon-tidal flat, and carbonate platform were summarized according to their combination characteristics. Additionally, 12-14 fourth-order sequences and three third-order sequences CSI, CSII, and CSIII were divided, and a sequence stratigraphic framework of the Lopingian coal-bearing series was established. Among them, the features of third-order sequence CSIII paleogeography from west to east are alluvial plains, deltas, lagoon-tidal flats, and limited carbonate platforms. Thick coal seams are mainly developed in the sedimentary environment of tidal flats, delta plains, and floodplains behind banks. Closely related to coal seam thickness, gas contents of Lopingian coal seams are generally higher than 8 m3/t, except the low level in northwest and partial denudation areas. CBM accumulation is significantly controlled by the fold structure, and the hydraulic plugging effect makes the syncline core favorable for CBM accumulation. Furthermore, favorable geostress conditions enable the secondary anticline to become a favorable area for CBM accumulation when the sealing conditions are better. This research will provide a theoretical guide for the exploration and development of CBM in the study area.